(3eYQGL GdefgGLs - (3fGUQ GdOjf GdTjQGRis; (3GdHjVGhj , YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, fGUQ GdOjf CHh SYjO,J (B685 (3g` ? s ((3CMeO Hf eMeO Hf eMeO Hf ejSi Hf eQJVi s)
(3ChdgG (B:s
(3hHYO aEffi hbaJ Ydi eNJUQ ai CUhd Gdabg ddEeGe GdYGde fGUQ GdOjf eMeO GdTjQGRi s
(3BNQgG (B:s
(3ef gPg GdeSCdI ef GdcdGe eGdGeMdg TQa gPg GdChQGb Je GdcJGH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B97s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs